Differences in nitrogen‐assimilating enzyme activity in halophyte species are habitat‐related. Issue 5 (22nd July 2014) - Cott, Grace M.; Chapman, Deborah V.; Jansen, Marcel A. K.
Abstract The chemical form and content of available nitrogen (N) in salt marsh substrates varies considerably. On the western coast of Ireland, habitats designated as Ombrogenic Atlantic salt marshes were formed on ombrogenic peat substrate. The peat substrate in these systems has three times more ammonium than substrate from adjacent salt marsh habitats on sand and mud substrate. This study examined the extent to which the high concentration of ammonium in peat salt marsh substrate influences the N‐ assimilating enzyme activity of halophytes and the extent to which N metabolism differs between species. Specifically, this work investigated whether plants from peat salt marshes are more likely to assimilate ammonium than plants from non‐peat substrates. Four halophyte plant species—Armeria maritima, Aster tripolium, Plantago maritime, and Triglochin maritime—were sampled from various saltmarsh habitats including three sites on peat substrate and three on non‐peat substrate, comprising sand, mud and sand/mud. The activities of N‐metabolising enzymes—glutamine synthetase (GS), glutamate synthase, glutamate dehydrogenase (GDH), and nitrate reductase (NR)—were quantified in shoot and root parts. Root GS activity in Armeria maritima and shoot GS activity in Triglochin maritima were positively correlated with increasing soil ammonium levels. Root NR activity in Aster tripolium and shoot NR activity in Plantago maritima were significantly higher in plants grown on non‐peat substrates than peat substrates. The shoot : root GS activity ratio in Triglochin maritima on peat substrate was more than double the ratio on non‐peat substrates. It is concluded that all species tested displayed differences in N‐metabolising activities depending on the chemical form and/or concentration of N in the substrate, while three out of the four species were capable of taking advantage of the high levels of ammonium in peat substrates.